Modulation of the Cytotoxic Properties of Pd(II) Complexes Based on Functionalized Carboxamides Featuring Labile Phosphoryl Coordination Sites - Diana V. Aleksanyan; Aleksandr V. Konovalov; Svetlana G. Churusova; Ekaterina Yu. Rybalkina; Alexander S. Peregudov; Svetlana A. Aksenova; Evgenii I. Gutsul; Zinaida S. Klemenkova; Vladimir A. Kozlov (MDPI AG, 2023)
Platinum-based drugs are commonly recognized as a keystone in modern cancer chemotherapy. However, intrinsic and acquired resistance as well as serious side effects often caused by the traditional Pt(II) anticancer agents prompt a continuous search for more selective and efficient alternatives. Today, significant attention is paid to the compounds of other transition metals, in particular those of palladium. Recently, our research group has suggested functionalized carboxamides as a useful platform for the creation of cytotoxic Pd(II) pincer complexes. In this work, a robust picolinyl- or quinoline-carboxamide core was combined with a phosphoryl ancillary donor group to achieve hemilabile coordination capable of providing the required level of thermodynamic stability and kinetic lability of the ensuing Pd(II) complexes. Several cyclopalladated derivatives featuring either a bi- or tridentate pincer-type coordination mode of the deprotonated phosphoryl-functionalized amides were selectively synthesized and fully characterized using IR and NMR spectroscopy as well as X-ray crystallography. The preliminary evaluation of the anticancer potential of the resulting palladocycles revealed a strong dependence of their cytotoxic properties on the binding mode of the deprotonated amide ligands and demonstrated certain advantages of the pincer-type ligation.